Program Evaluation on Learning Materials, Tutors, Assessment Matters and Overall Program Structure from ODL Students' Perspective - Wirawani Kamarulzaman; Wong, Huey Siew (2020)
Open Distance Learning (ODL) is an approach in education practices in Open University Malaysia (OUM). One of its programs that are offered through ODL is the Bachelor of Psychology (BPSY) and it is one of the programs with the highest student intake in OUM. Since the program has been commencing for more than 10 years, it is the time to evaluate whether the program needs any revisions or improvements. Thus, the aim of the study is to determine the level of satisfaction of students on the Psychology program offered in OUM. A questionnaire was developed for this purpose which includes 4 areas of students' satisfaction, namely the learning materials, student perceptions on their tutors, assessment matters, as well as the overall program structure. The questionnaires were distributed to more than 1000 active students through online and face-to-face tutorials. A total of 439 students participated in the study. The results indicated that students are most satisfied with the overall program structure and least satisfied with the assessment matters with the mean score of 3.98 and 3.59 respectively. The study certainly benefits the university in taking action to revise and improve the program. Recommendation for future research is included at the end of the paper. (Abstract by authors)